Use of Software Reliability Growth Model to Estimate the Reliability of Electric Vehicle - Divya Dhyani, Viresh Sharma (International Journal of Advanced Science and Technology, 2020)
There is a huge consumption of natural resources in and across the country. The foremost consumption is of oil, which is primarily used for transportation in every part of the world. Increasing population and increase in living standard of the middle class people has lead to the increase in demand of vehicles and in return oil. This increasing demand lead to the innovation of a new technology vehicle, which emerges as an opportunity for economic development benefits. After oil, there is an alternate source of energy- electricity –which seems to be a beneficial investment. Not only in terms of energy (oil)conservation, use of electric vehicles proves/ will prove to be a beneficial step in terms of pollution control and interdependency of one country on oil imports. This paper discuses types of electric vehicles, their differences and their working